Composite thermal interface material based on metal aerogel as well as preparation method and application of composite thermal interface material

By using metal aerogel and high thermal conductivity in thermal interface materials, composite thermal interface materials with high thermal conductivity and excellent flexibility are prepared, which solves the problems of insufficient thermal conductivity and poor compliance of existing materials in high-power chip packaging, and improves heat dissipation performance and production stability.

CN119566293AActive Publication Date: 2025-03-07HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411758829.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing thermal interface materials have problems such as insufficient thermal conductivity, poor flexibility, poor mechanical properties, chemical compatibility problems, mismatched thermal expansion coefficient, insufficient electrical insulation, difficult thickness and uniformity control, poor environmental stability, and insufficient compatibility and interface adhesion in high-power chip packaging, which affects the heat dissipation effect and equipment reliability.

Method used

The composite thermal interface material based on metal aerogels is obtained by preparing metal hydrogels, blending with highly thermally conductive particles, and mechanical cutting and laser processing. The material has a three-dimensional thermal conductivity network structure, which improves thermal conductivity and flexibility.

Benefits of technology

It achieves high thermal conductivity and excellent flexibility, reduces the interface thermal resistance of thermal interface composite materials, improves the heat dissipation performance and production stability of chip packaging, and solves the problems of high thickness, large thermal resistance and flux volatility of traditional thermal grease and thermal gaskets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566293A_ABST
    Figure CN119566293A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal interface materials, in particular to a composite thermal interface material based on metal aerogel and a preparation method and application of the composite thermal interface material. The composite thermal interface material based on the metal aerogel prepared by the invention has excellent flexibility. Compared with a conventional polymer-based heat-conducting pad in the prior art, a three-dimensional heat-conducting network formed by the metal aerogel greatly improves the deformability of the composite thermal interface material, the composite thermal interface material can be adaptively attached to the surface of a complex structure, better processing conditions and process results are achieved, and the interface thermal resistance of the thermal interface composite material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal interface materials, and in particular to a composite thermal interface material based on metal aerogel, and a preparation method and application thereof. Background Art

[0002] Thermal interface material (TIM) is a type of material used to improve heat transfer efficiency in electronic devices. When two solid surfaces come into contact, due to the microscopic unevenness of the surface, only a few points are actually in contact, and the gaps between these points will be occupied by air. The thermal conductivity of air is very low, which will form the so-called "contact thermal resistance" and hinder the effective transfer of heat. The role of thermal interface materials is to fill these tiny gaps and exclude air, thereby providing a low thermal resistance path so that heat can be more efficiently transferred from the heat source (such as an integrated circuit chip) to the radiator or cooling system. The use of such materials is critical to ensuring temperature management of electronic components, as overheating can affect the performance, stability and life of electronic components. Common thermal interface materials include thermal grease, thermal gel, silicone-free thermal pads, thermal phase change materials, thermal elastomer materials, thermal silicone cloth and carbon fiber thermal pads.

[0003] Thermal interface materials in the chip packaging field play a vital role in the current industrial development. Their performance is directly related to the heat dissipation effect, stability and overall performance of the chip. The current status of the thermal interface material industry presents a series of key trends, which are mainly analyzed from two important perspectives: thermal conductivity and flexibility.

[0004] First of all, thermal conductivity is one of the important indicators for evaluating the performance of thermal interface materials. As the power density of chips continues to increase, the demand for higher thermal conductivity is also gradually increasing. Among traditional thermal interface materials, metal oxides and silicone grease are still common choices with relatively high thermal conductivity. However, in order to meet the heat dissipation needs of high-performance chips, more and more research is focused on introducing new high thermal conductivity materials, such as diamond and boron nitride. These new materials, with their excellent thermal conductivity performance, can effectively improve the heat dissipation performance of chip packaging and drive the industry towards a more efficient direction.

[0005] Secondly, flexibility is another aspect that has received much attention. During the chip packaging process, the thermal interface material needs to be able to adapt to the slight deformation between the chip and the packaging substrate to ensure good physical contact and heat conduction. Materials with good flexibility help fill microscopic unevenness and reduce thermal stress caused by temperature changes. Traditional silicone grease performs well in terms of flexibility, but its thermal conductivity is relatively low. Therefore, in recent years, researchers have begun to pay attention to new thermal interface materials that have both high thermal conductivity and flexibility. Although some emerging materials such as graphene have excellent flexibility and thermal conductivity, they still face cost and production difficulties when used on a large scale. Therefore, improving flexibility while keeping costs controllable has become an urgent problem to be solved in current research and development.

[0006] In addition, there are some potential defects and challenges in thermal interface materials in the chip packaging field, such as (1) Volatility and aging: Many TIMs contain volatile components, which may precipitate or evaporate after long-term use, resulting in degradation of material performance and increased thermal resistance. (2) Mechanical properties: TIMs may not have sufficient mechanical strength to maintain stable performance under long-term pressure or vibration environments. During repeated thermal cycles, TIMs may deform or harden, resulting in increased contact thermal resistance. (3) Chemical compatibility: Certain components in TIMs may react with other materials in chip packaging (such as metals, plastics, ceramics, etc.), causing corrosion or decomposition. (4) Mismatch in thermal expansion coefficients: The mismatch in thermal expansion coefficients between TIMs and adjacent materials may lead to stress accumulation, causing delamination, cracks, or packaging failure. (5) Electrical insulation: Although most TIMs are designed to be electrically insulating, some materials may lose their insulating properties under certain conditions (such as humidity and temperature), causing short circuit risks. (6) Thickness and uniformity: The thickness of TIMs must be properly controlled. Too thick will lead to reduced thermal conductivity efficiency, while uneven thickness will lead to uneven heat flow distribution, affecting the overall heat dissipation effect. (7) Environmental stability: TIMs may have unstable performance under extreme environmental conditions (such as high and low temperatures, high humidity, and corrosive gases), affecting long-term reliability. (8) Compatibility and interface adhesion: TIMs need to maintain good adhesion with the chip and heat sink surface, otherwise it may cause delamination or fall off, affecting heat conduction.

[0007] In general, thermal interface materials for chip packaging are developing towards high thermal conductivity, superior flexibility and other comprehensive properties. This development momentum will provide more efficient and reliable heat dissipation solutions for electronic devices, and promote innovation and progress in the semiconductor industry. Therefore, new thermal interface materials that can comprehensively solve the above problems are needed. Summary of the invention

[0008] The first aspect of the present invention provides a method for preparing a composite thermal interface material based on metal aerogel, comprising the following steps:

[0009] S1. preparing a metal hydrogel, washing and drying the metal hydrogel to obtain a metal aerogel;

[0010] S2. dispersing the highly thermally conductive particles in an organic carrier to obtain a mixture, blending the mixture with the metal aerogel and allowing it to stand and soak, and then resetting the solution to obtain a metal hydrogel-based composite material;

[0011] S3. The metal hydrogel-based composite material is dried to obtain a metal aerogel-based composite material, and the composite thermal interface material is obtained by mechanical cutting and laser processing;

[0012] In some embodiments, the metal material of the metal hydrogel is at least one of silver, copper, nickel, gold, and tin.

[0013] The present invention does not specifically limit the preparation method of the metal hydrogel, and the metal hydrogel may be prepared by a common method in the art, such as a chemical in-situ reduction method.

[0014] In some embodiments, the metal hydrogel is prepared by a chemical in-situ reduction method: PVP, AgNO3, and FeCl3 are dissolved in ethylene glycol and stirred evenly, and then placed in a drying oven and reacted at 120-150° C. for 3-5 hours to obtain the metal hydrogel.

[0015] In some embodiments, the cleaning is performed by first soaking in a saline solution for 3-8 times, each time for 5-15 minutes, and then soaking in alcohol for 5-15 minutes; the saline solution is a 0.002M NaBH4 aqueous solution or a 0.1M NaCl aqueous solution.

[0016] In some embodiments, the drying is to freeze the prepared metal hydrogel with liquid nitrogen, vacuum dry or supercritical dry to prepare the metal aerogel.

[0017] In some embodiments, the high thermal conductivity particles include at least one of Ag, Cu, Ga, and GaInSn;

[0018] In some embodiments, the volume ratio of the high thermal conductive particles in the composite thermal interface material is 40-80%.

[0019] Both metal nanoparticles and metal nanowires have high specific surface areas, which makes them have high surface activity, which promotes the interaction between particles and wires, so that metal nanoparticles can be adsorbed on metal nanowires.

[0020] In some embodiments, the particle size of the highly thermally conductive particles is 0.5 μm-13 μm.

[0021] In some embodiments, the organic carrier includes an organic solvent and a stabilizer, the organic solvent includes at least one of methanol, ethanol, ethylene glycol, isopropanol, and butanediol, and the stabilizer includes at least one of polyvinyl pyrrolidone, citric acid, sodium citrate, polyethylene glycol, hexadecyltrimethylammonium chloride, and sodium dodecyl sulfate.

[0022] Preferably, the organic solvent is ethanol, and the stabilizer is citric acid.

[0023] In some embodiments, the specific preparation method of the mixture is: dispersing 0.5 g of high thermal conductive particles in a mixed solution of 30 mL of ethanol and 0.1 g of citric acid, and ultrasonically dispersing at 50-300 W for 1-30 min to obtain the mixture.

[0024] In some embodiments, the static soaking time is 1-16 hours, and ultrasound, stirring and liquid phase peristalsis equipment are loaded simultaneously to promote liquid phase flow and dispersion.

[0025] In some embodiments, the drying time in S3 is 0.5-5 h, and the drying method is freeze drying or supercritical drying.

[0026] In some embodiments, the laser processing power is 5-30 W; the laser processing speed is 50 mm / min-200 mm / min.

[0027] The second aspect of the present invention provides a composite thermal interface material based on metal aerogel, which is obtained by the above-mentioned preparation method.

[0028] In some embodiments, the thermal resistance of the composite thermal interface material is 0.16°C·cm 2 / W, elastic modulus is 400Pa.

[0029] In some embodiments, the interior of the composite thermal interface material is a three-dimensional porous structure formed by cross-linking of nanowires, and the diameter of the nanowires is 30-550 nm.

[0030] The third aspect of the present invention provides application of the above-mentioned composite thermal interface material in the semiconductor field.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The metal aerogel-based composite thermal interface material prepared by the present invention is a key material to ensure stable heat dissipation of electronic systems in the semiconductor field. Different from the paste-like thermal grease and the traditional thermal pad (0.5mm) with higher modulus and larger thickness in the prior art, the new thermal pad of the present invention has a single component, a low thickness in the bonding area (30μm), no fluidity, and anti-aging. There is no liquid pumping out, flux volatilization and other phenomena in the packaging process. It can solve the pain points of traditional thermal grease paste pumping out, high thickness and high thermal resistance of thermal pads, and flux volatilization during the use of indium sheets, and thus has better production stability and performance reliability.

[0033] 2. The composite thermal interface material based on metal aerogel prepared by the present invention has excellent flexibility. Compared with conventional polymer-based thermal conductive pads in the prior art, the three-dimensional thermal conductive network formed by metal aerogel greatly improves the deformability of the composite thermal interface material. Therefore, the skeleton structure constructed based on metal aerogel can exert excellent thermal conductivity on the one hand, and on the other hand, it can quickly fill the gap between the device and the heat sink, fit tightly with the solid surface, and eliminate local structural mismatch and assembly stress. For non-planar structural connections, the present invention has outstanding advantages, can adaptively fit complex structural surfaces and has better processing conditions and process results, and reduces the interface thermal resistance of thermal interface composite materials.

[0034] 3. The metal aerogel-based composite thermal interface material prepared by the present invention is metal nanoparticles, which further improve the thermal conductivity of the thermal interface material and can be used for heat dissipation of high-power devices and high-performance reliability connections. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 a is a macroscopic image of the dried nanosilver aerogel prepared in Example 1, Figure 1 b is the electron microscope image of the interior of the dried nanosilver aerogel.

[0036] Figure 2 Schematic diagram of silver nanoaerogel composite nanoparticles.

[0037] Figure 3 Schematic diagram of the composite thermal interface material after the nanosilver aerogel is composited with nanoparticles.

[0038] Figure 4 This is a surface micrograph of the composite thermal interface material after the nanosilver aerogel is composited with nanoparticles. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] This embodiment provides a composite thermal interface material based on metal aerogel, and the preparation method includes the following steps:

[0042] S1. Preparation of nanosilver hydrogel by chemical in situ reduction method: 0.2g PVP, 0.5g AgNO 3、 0.2g FeCl3 was dissolved in 50mL ethylene glycol and stirred evenly, then placed in a drying oven and reacted at 130°C for 4h to obtain nanosilver hydrogel, the nanosilver hydrogel was soaked in 0.002M NaBH4 aqueous solution for 5 times, each time for 10min, and a new NaBH4 aqueous solution was replaced each time, and finally soaked in alcohol for 10min; after cleaning, supercritical drying was performed, and the nanosilver aerogel of 25mm*25mm*5mm was cut;

[0043] The macroscopic image of the dried nanosilver aerogel is shown in Figure 1 a, Electron microscope image of the interior of the dried nanosilver aerogel Figure 1 b, The diameter of silver nanowires is 30-550nm.

[0044] The internal microscopic diagram of the dried nanosilver aerogel is shown in Figure 2 As can be seen from the figure, the overlap of wires inside the aerogel ensures the formation of a heat conduction path.

[0045] S2. 0.5 g of liquid metal GaInSn nanoparticles are dispersed in a mixture of 30 mL of ethanol and 0.1 g of citric acid by ultrasonic dispersion to obtain a mixture. The ultrasonic time is 10 min, the power is 50 W, and the diameter of the nanoparticles is 2-7 um. The mixture is blended with nanosilver aerogel and allowed to stand and soak for 2 h. During the soaking process, the nanoparticles are compounded on the surface of the aerogel to obtain a nanosilver hydrogel-based composite material. The volume proportion of the GaInSn nanoparticles in the nanosilver hydrogel-based composite material is 80%.

[0046] S3. The nanosilver hydrogel-based composite material is then dried by a supercritical drying method to obtain a nanosilver aerogel-based composite material, and the composite thermal interface material is obtained by mechanical cutting and laser processing;

[0047] The processing power of the laser processing is 20W; the laser processing speed is 100mm / min.

[0048] Schematic diagram and macroscopic diagram of composite thermal interface material after composite nanoparticles of silver nano-aerogel Figure 3 and Figure 4 As can be seen from the figure, the particles are mainly compounded on the surface of the aerogel. There are contact points between the particles and between the particles and the nanowires, which increases the heat conduction path on the basis of the nanowire aerogel.

[0049] Example 2

[0050] This embodiment provides a composite thermal interface material based on metal aerogel, and the specific implementation manner is the same as that of Embodiment 1, except that:

[0051] S2. 0.5g of liquid metal GaInSn nanoparticles are dispersed ultrasonically in a mixture of 30mL of ethanol and 0.1g of citric acid to obtain a mixture, the ultrasonic time is 10min, the power is 50W, and the diameter of the nanoparticles is 2-7um. The silver aerogel is soaked in an ethanol solution, and then the liquid metal GaInSn mixed solution is slowly added to the nanosilver wire aerogel ethanol solution at a flow rate of 10-300μL / s through a self-fluid device, and the liquid metal is dispersed and filled into the nanosilver wire aerogel three-dimensional network structure using ultrasound (power 20W, frequency 40kHz), and the volume proportion of GaInSn nanoparticles in the nanosilver hydrogel-based composite material is 60%.

[0052] In addition to the advantages of Example 1, this embodiment has the advantages that the self-fluid device can accurately control the flow rate of the liquid metal particle mixture, thereby controlling the amount of liquid metal compounded on the surface of the metal aerogel.

[0053] Comparative Example 1

[0054] The specific implementation of this comparative example is the same as that of Example 1, except that the ultrasonic power in S2 is 50 W; Cu particles are used to replace the liquid metal GaInSn nanoparticles, and the volume ratio of Cu particles in the nanosilver hydrogel-based composite material is 80%.

[0055] Comparative Example 2

[0056] The specific implementation of this comparative example is the same as that of Example 1, except that the ultrasonic power in S2 is 50 W; Ga particles are used to replace the liquid metal GaInSn nanoparticles, and the volume proportion of Ga particles in the nanosilver hydrogel-based composite material is 80%.

[0057] Comparative Example 3

[0058] The specific implementation of this comparative example is the same as that of Example 1, except that the ultrasonic power in S2 is 50 W; Ag particles are used to replace the liquid metal GaInSn nanoparticles, and the volume ratio of Ag particles in the nanosilver hydrogel-based composite material is 60%.

[0059] Comparative Example 4

[0060] The specific implementation of this comparative example is the same as that of Example 1, except that the ultrasonic power in S2 is 90 W; and the volume proportion of the GaInSn particles in the nano-silver hydrogel-based composite material is 30%.

[0061] Performance Testing

[0062] The composite materials prepared in the above examples and comparative examples were subjected to the following tests, and the results are shown in Table 1:

[0063] Thermal resistance: The thermal resistance of the material was tested using the total thermal resistance steady-state method using the interface material thermal conductivity and thermal resistance measuring device LW-9389 (LongWin Co., Ltd. China) designed based on the ASTM-D5470 standard test method.

[0064] Elastic modulus: Use a universal testing machine to test and measure the stress and strain during the material compression process. The elastic modulus is calculated by analyzing the stress-strain curve.

[0065] Thickness: Measured by nanometer thickness meter.

[0066] Compression amount: The ratio of the difference in material height before and after compression to the original thickness of the material, that is, the size reduced by compression in the height direction / original thickness of the material × 100%.

[0067] Table 1

[0068] Thermal resistance Elastic modulus(Pa) Example 1 <![CDATA[0.16℃·cm 2 / W]]> 408 Example 2 <![CDATA[0.17℃·cm 2 / W]]> 412 Comparative Example 1 <![CDATA[0.3℃·cm 2 / W]]> 513 Comparative Example 2 <![CDATA[0.5℃·cm 2 / W]]> 526 Comparative Example 3 <![CDATA[0.25℃·cm 2 / W]]> 857 Comparative Example 4 <![CDATA[0.27℃·cm 2 / W]]> 647

[0069] From the above performance test results, it can be seen that the composite thermal interface material of Example 1 has excellent flexibility and conductivity. This is mainly because the three-dimensional thermal conductive network formed by the metal aerogel greatly improves the deformability of the composite thermal interface material and can exert excellent thermal conductivity.

[0070] However, the comparative example did not adopt the necessary technical solutions, resulting in that its corresponding performance tests were significantly worse than those of the embodiments. In comparative example 1, the ultrasonic power and the type of conductive particles were changed, and it can be seen that the conductive effect and the flexibility effect were reduced to varying degrees, which proves that the solution of embodiment 1 has an important influence on the effect of the present invention.

[0071] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite thermal interface material based on metal aerogel, characterized in that: The steps include: S1. preparing a metal hydrogel, washing and drying the metal hydrogel to obtain a metal aerogel; S2. dispersing the highly thermally conductive particles in an organic carrier to obtain a mixture, soaking and blending the mixture with the metal aerogel, and then resetting the solution to obtain a metal hydrogel-based composite material; S3. The metal hydrogel-based composite material is dried to obtain a metal aerogel-based composite material, and the composite thermal interface material is obtained by mechanical cutting and laser processing; The high thermal conductivity particles include at least one of Ag, Cu, Ga, and GaInSn; The volume proportion of the high thermal conductivity particles in the composite thermal interface material is 40-80%.

2. The preparation method according to claim 1, characterized in that: The metal material of the metal hydrogel is at least one of silver, copper, nickel, gold and tin.

3. The preparation method according to claim 2, characterized in that: The particle size of the high thermal conductive particles is 1 μm-5 μm.

4. The preparation method according to claim 3, characterized in that: The organic carrier includes an organic solvent and a stabilizer, the organic solvent includes at least one of methanol, ethanol, ethylene glycol, isopropanol, and butanediol, and the stabilizer includes at least one of polyvinyl pyrrolidone, citric acid, sodium citrate, polyethylene glycol, hexadecyltrimethylammonium chloride, and sodium dodecyl sulfate.

5. The preparation method according to claim 4, characterized in that: The static soaking time is 1-16h.

6. The preparation method according to claim 5, characterized in that: The drying time in S3 is 0.5-5h.

7. A composite thermal interface material based on metal aerogel, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 6.

8. The composite thermal interface material according to claim 7, characterized in that: The thermal resistance of the composite thermal interface material is 0.16-2.0°C·cm 2 / W, elastic modulus is 400~1400Pa, and compression is 80~99.6%.

9. The composite thermal interface material according to claim 7, characterized in that: The interior of the composite thermal interface material is a three-dimensional network structure formed by cross-linking nanowires, and the diameter of the nanowires is 30-550nm.

10. Application of the composite thermal interface material according to claim 7 in the semiconductor field.

Citation Information

Patent Citations

  • Preparation and packaging method of metal aerogel coated liquid metal heat-conducting adhesive

    CN112694858A

  • Polymer-based metal aerogel composite thermal interface material and preparation method thereof

    CN112745636A

  • Flexible heat conduction pad and preparation method thereof

    CN115403931A

  • Thermally conductive filler, thermally-conductive composite material, wire harness, and method for manufacturing thermally conductive filler

    US20230365852A1